Ultrasonographic evaluation of ovulation stigma and prognosis of growth outcomes of the dominant follicle - О. В. Булавенко; В. В. Дощечкин (Publishing House TRILIST, 2017)
Study objective: To study the relationship of ultrasonographic changes in the walls of the dominant follicle with the outcomes of its growth - ovulation or persistence. Study design: Prospective cross-sectional study. Patients, Methods, Settings: Upon results of sonographic one cycle pre-assessment, 96 women from subfertile couples were distributed into two groups. Main group - 78 women with documented ovulation. Comparison group consisted of eighteen women with various clinical forms of follicle persistence. Ovulation stigma identification was performed by transvaginal ultrasonography using the technique of Mobile Hydroacoustic Window (TVS+MHAW) with standard 6-10 MHz probes. Three sources of fluid were used for the building of mobile hydroacoustic window: antral fluid, contents of ovulation stigma and the fluid located close to ovary apex. Subtle structures of follicle walls were assessed at the interface of liquid and dense medium in the area of ovary apex. Results, Discussion: In 52 cases (66.6%) two main types of ovulation stigma - Bleb-type and Flat-type were identified, in 48 (61.5%) and 4 (5.1%) cases, accordingly. In the rest of 26 (33.3%) ovulating women it was not possible to identify the stigma sonographically. In 18 (18.8%) cases anovulatory cycles were presented: LUF in 10 (10.4%) cases, follicular regression in 6 (6.3%) and haemorrhagic cysts developed in two cases (2.1%). Local thinning of follicular walls in the area of stigma (91%), appearance of small amount of fluid near the ovary apex (93.6%) and elongated or cone-like shape of the pre-ovulatory follicle (59%) were the most prevalent sonographic signs of stigma formation. Stages of sonographic changes of the structure of forming ovulation stigma were detected and described. New sonographic sign of ovulation stigma, - the phenomenon of Constriction Ring (30.8%), characterizing the closing stage of stigma formation was described. Mean growth and regression rates were calculated for dominant follicles. The increase of dominant follicle size beyond 28.5 mm is connected to high risk of its anovulation or persistence. It should also be taken into account that ovulation can occur at any stage of stigma formation, also without its sonographic appearance. Conclusion: The study of phenotypic features of stigma formation by means of TVS + MHAW can be useful for timing of OPU in IVF natural cycles and prediction of high risk of follicle persistence/regression at intrauterine insemination.